n-1 . Prove that t(t+1) = n(n-1) (n...
Question
Fullscreen

n-1 . Prove that t(t+1) = n(n-1) (n+1) for all natural for all natural numbers n > 2. 1 = 1

11th - 12th Class
Maths
Solution
96
Rating
4.0 (1 ratings)
Fullscreen
( k>3 ) ( =(4-2)(n-1+2)(2(n-1)+1) ) ( frac{(n-1)(n) times 3}{2 times 3} ) ( frac{2}{frac{n-1}{6}} frac{(2 n-1)}{6}+frac{3 n(n-1)}{6} ) ( =frac{n(n-1)}{6}[24-1+3] ) ( =frac{n(n-1)}{6}(2 n+n)=frac{n(n-1)(n+1)}{3} ) Teacher Signat
Quick and Stepwise Solutions Just click and Send Download App OVER 20 LAKH QUESTIONS ANSWERED Download App for Free